Geological characterization of the distribution of albian carbonatic reservoirs, Southwest of Campos Basin (Brazil). - Habermann, Leonardo [UNESP]; Vincentelli, Maria Gabriela Castillo [UNESP]; Contreras, Sergio Antonio Cáceres [UNESP]; Perinotto, José Alexandre de Jesus [UNESP] (My University, 2018)
In the southwestern region of the Campos Basin, carbonate reservoirs are conditioned by structural and stratigraphic features. In this sense, it is intended to characterize the distribution and type of play associated to the main reservoir of this nature, identified based on a geological-geophysical analysis in an area that contains eight mature oil fields located in the region of studies. The present work aims the characterization of mechanisms that allow the local accumulations of hydrocarbons in a main reservoir level, of generalized occurrence in the area. This objective was reached through the analysis of geophysical profiles, well correlation and 2D and 3D Seismic interpretation, which allowed the verification of predominance of structural traps in Pampo and Linguado fields, related to a regional dome feature, and in Bicudo, where the producer level occurs on a rollover structure. In Enchova and Bonito fields, mixed traps were described for the observed accumulations, with presence of elevated features (structural component) associated to lateral facies variation in depositional lows (stratigraphic component). It was verified that, although the Enchova Canyon, of Oligocene age, constitutes a stratigraphic feature of wide occurrence in the Enchova, Enchova Oeste, Bicudo and Bonito, important in the hydrocarbon trapping of Paleogen/ Neogen strata, in the region studied this feature does not control the reservoir levels of the Quissamã Formation.
Caracterização geológica da distribuição de reservatórios carbonáticos albianos, Sudoeste da Bacia de Campos (Brasil).
Keywords: Campos basin; Quissamã formation; Traps; Well logs